1988
DOI: 10.1002/1097-4679(198809)44:5<674::aid-jclp2270440503>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual distraction in schizophrenia

Abstract: The purpose of this project was to determine whether a distractibility deficit at the stimulus‐identification level could be identified in schizophrenics after distractor and non‐distractor conditions had been matched for difficulty (N = 110). Process schizophrenics, reactive schizophrenics, and psychiatric controls were asked to identify tachistoscopically presented stimuli shown with and without distractors. The distractor and non‐distractor tasks were matched for difficulty beforehand by manipulating presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
4

Year Published

1995
1995
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
1
0
4
Order By: Relevance
“…161Á184) found that patients made less intrusion errors (report the name of a distractor instead of the target) than controls. This is consistent with a study (Watson et al, 1988) in which patients were asked to identify a briefly displayed target letter embedded in distractors made of letter pieces. Patients with schizophrenia did not show more deficits under the distractor condition than nonschizophrenic control patients.…”
Section: Introductionmentioning
confidence: 99%
“…161Á184) found that patients made less intrusion errors (report the name of a distractor instead of the target) than controls. This is consistent with a study (Watson et al, 1988) in which patients were asked to identify a briefly displayed target letter embedded in distractors made of letter pieces. Patients with schizophrenia did not show more deficits under the distractor condition than nonschizophrenic control patients.…”
Section: Introductionmentioning
confidence: 99%
“…bölgeyi değil, değişik bölgelerdeki nöronların entegre çalıştığı nöro-nal şebeke sistemini anlamaktayız (3,5,7,8). SSS'deki bölgeler bir işle-vin tamamlanması sürecindeki basamaklardan birinde herhangi bir işleve daha yatkın olacak şekilde yerlerini almışlardır.…”
unclassified
“…Bu bölgelerin herbiri çevremizin planını çıkartma işle-minde değişik koordinat sistemleri kullanır (3,5,8). Örneğin PG ekstrapersonel uzayın sensoryal reprezantasyonunu, FEF oryante edici ve araştırıcı hareketlerin dağıtımı için bir haritalamayı ve singülar (limbik komponent) bölüm de uzaysal koordinatların bizim için değerini belirten haritalamayı yapar (5).…”
unclassified
See 2 more Smart Citations